Impacto del puñetazo y de la patada en los deportes de combate: una revisión sistemática - Marques-Junior, N. K. (Pensar en movimiento: Revista de Ciencias del Ejercicio y la Salud, 2021)
The objective of the systematic review was to present the punch and kick impact of some combat sports. The studies were identified in electronic databases from September 2018 to August 2019. Literature searches were conducted in Google Scholar, Research Gate, and PubMed. The systematic review had 19 scientific articles. The greater punch impact of the male fighter was of the boxing straight with 4800 ± 601 newtons (N). Female fighter the greater punch impact was of the boxing jab with 1170.7 ± 165.3 N. The kick impact of the female taekwondo (TKD) had a greater result of the tui tchagui with 2490.3 ± 846.2 N and in the male had a greater result of the TKD bandal tchagui impact of 6400 ± 898 N. In conclusion, the punch and kick impact of combat sports is an important content for the athlete to know the most effective attack.